Person-Centered Therapy and Personal Growth - Narknisorn, Boontarika (Journal of Social and Development Sciences, 2012)
Person-centered therapy enhances humans’ personal growth toward self-actualization and deepens quality personal relationship. This article aims to (1) explain the concepts of person-centered therapy and (2) link its contribution to humans’ personal growth and healthy relationship. Personcentered therapy believes in human’s positive qualities as being trustworthy and owning ‘inner resources’ to pursue ‘self-actualization and health.’ The therapeutic goals are to assist clients to be true to themselves and acquire their full potentials. Person-centered therapy emphasizes the qualities of the therapist and therapeutic relationship as the most powerful components to help clients grow. The therapist needs to maintain positive attitudes, to believe in client’s potentials and motivation to become actualized, to accept one’s and others’ uniqueness and needs and to be trustworthy, warm, open and kind. Person-centered therapy reflects that pain and obstacles in life are necessary and can stimulate humans to grow. Person-centered therapy helps the therapist; clients and humans pursue self-actualization and possess better humans’ qualities, which can contribute to world peace as Rogers hoped.